Effects of Exogenous Trehalose on Plant Growth, Physiological and Biochemical Responses in Gardenia Jasminoides Seedlings During Cold Stress - Dejian Zhang; Jianhao Zheng; Qingping Yi (Horticulturae, 2025)
In order to explore the effect and mechanism of trehalose (Tre) on the growth and cold resistance of gardenia jasminoides Ellis under low-temperature stress, 15 mmol/L of Tre was used on gardenia seedlings under different degrees of low-temperature stress. The results show that −3 °C (low-temperature stress) significantly inhibited the growth of gardenia, while Tre at 15 mmol/L restored the plant height, number of leaves, total plant weight, and fresh weight of above ground and underground parts to 88.10%, 81.05%, 98%, 87.61% and 96.68% at 20 °C (normal temperature conditions). The total length of the root, number of lateral roots, total root surface area and root volume recovered to 88.48%, 74.08%, 104.03% and 83.77% under normal temperature at 20 °C. The chlorophyll content, chlorophyll fluorescence parameters and photosynthetic intensity parameters in the leaves of gardenia jasminoides were significantly decreased under low-temperature stress at −3 °C, while the contents of chlorophyll a, chlorophyll b and total chlorophyll were significantly increased under 15 mmol/L Tre treatment. Meanwhile, chlorophyll fluorescence parameters (φPSII, Fv′/Fm′ and qP increased by 18.60%, 73.17% and 81.82%, respectively) and photosynthetic intensity parameters (Pn, Gs, Ci and Tr increased by 33.33%, 70.86%, 14.83% and 116.50%, respectively) were also increased. At −3 °C, Tre treatment significantly increased the activities of SOD, POD and CAT in roots, and reduced the content of reactive oxygen species (H2O2 and superoxide anion). At the same time, the contents of root osmotic regulatory substances (proline and malondialdehyde) were decreased by 15.16% and 12.65%, respectively. At −3 °C, Tre significantly increased the root auxin content and significantly decreased the trans-zeanoside content, but had no significant effects on gibberellin and abscisic acid. Tre can also regulate the content of root respiratory metabolites under low-temperature stress, increase the malic acid content by 96.77% under −3 °C, and decrease the succinic acid content by 56.34%. In conclusion, Tre reduces the content of ROS and its damage by improving the antioxidant capacity in roots and enhances the osmoregulation and stability of cell membranes by reducing the content of osmoregulation substances, hormones and aerobic respiratory metabolites in the root, thus enhancing the cold resistance of gardenia.